1981
DOI: 10.1002/bjs.1800681011
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent ulceration after highly selective vagotomy for duodenal ulcer

Abstract: Recurrent peptic ulceration was diagnosed in 9 per cent of 433 patients who were treated by elective highly selective vagotomy (HSV) for duodenal ulcer (DU) between 1969 and 1980. In 233 patients followed up for 5-12 years (12 per cent being lost to follow-up), the incidence of recurrence was 10.7 per cent. The site of recurrence was duodenal in 23 patients, pyloric in 4, gastric in 6 and combined duodenal and gastric in 2 (total of 35 patients). One patient presented with a perforation, l4 with haemorrhage an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0
1

Year Published

1982
1982
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 19 publications
4
13
0
1
Order By: Relevance
“…In this respect pH metry does not seem to lead further than preopera tive gastric secretion tests with stimulation by pentagastrin or sham feeding [3][4][5][6][7][8][9][10][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect pH metry does not seem to lead further than preopera tive gastric secretion tests with stimulation by pentagastrin or sham feeding [3][4][5][6][7][8][9][10][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…This nonrespective procedure leaves the stomach reser voir and the pyloric sphincter intact and has far fewer side effects when compared with other ulcer operations [1][2][3][4][5][6][7][8][10][11][12][13], However, the long-term studies in the late 1970s and early 1980s reported a higher rate of recurrences after PGV than after resection methods [3,5,7]. The inci dence of recurrence for duodenal ulcers after PGV has shown a wide variation from 5 to 20% in a number of retrospective studies [8,[10][11][12][13][14]. In the past, the poorly defined prepyloric ulceration was classified with the du odenal ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure can be difficult and tedious because each branch of the anterior and posterior vagus nerve must be individually dissected, ligated, and divided. Success of HSV depends on meticulous technique because leaving a single fundic nerve branch intact will allow continued acid secretion in the corresponding gastric secretory zone, leading to early recurrence [3,6]. In fact, many surgeons find laparoscopic HSV to be technically difficult and time consuming, especially in the obese patient.…”
mentioning
confidence: 99%